Gamification in Education industry - Pathak, Ms. Shipra; Aggarwal, Dr. Shalini (The journal of contemporary issues in business and government, 2021)
Gamification is the emerging trend these days in various sectors like service training, business, health, organisational management, politics, retail and education. Gamification is widely used in education these days so it is necessary to study the different aspects of it. In this study we are using secondary data to analyse the importance and process of gamification. Further in this study we will analyse the tools for gamification. The purpose of the study is to study the process of gamification, the software tools used in gamification. In the end it leads to the conclusion that Gamification is an efficient instrument to bring out constructive changes in attitude of students towards learning, improving their eagerness to learn. The outcomes of this are dual, one, they improve results and grasping power of the content and generate conducive environment for learning